A Story of their own: Adolescent Pregnancy and Child Welfare in Aboriginal Communities - Ordolis, Emilia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
The phenomenon of adolescent pregnancy and its relationship to child welfare in Aboriginal communities provides a useful lens through which to understand fundamental and structural problems with the current child welfare system in Canada. The following paper will examine the relationship between adolescent pregnancy and child welfare, investigate concerns with the current child welfare system, and look to the Convention on the Rights of the Child as a framework for conceptualizing alternative approaches.